PERCEPTION OF THE POOR ON HEALTH SERVICES IN MAKASSAR CITY - Riri Amandaria .; Mauliadi Ramli .; Ulfa Utami Mappe (Universitas Negeri Makassar, 2022)
AbstractThe poor are vulnerable to disease and easy to transmit various diseases due to lack of environmental hygiene, clean living behavior of people who are not yet entrenched, knowledge about health and education which is generally still low. This study aims to find out the perspective of the poor regarding the health services they have received so far and the efforts they have made to access the health services they have wanted so far. This type of research is descriptive qualitative research conducted in Makassar City. The informants in the research were carried out by purposive sampling, this study used observation data collection techniques, interviews and documentation. The analysis technique used is qualitative and descriptive data analysis techniques (pre-field analysis and field data analysis). The results of our research regarding the efforts of the poor in accessing the health services they have received so far are that in the field there are many irregularities in obtaining access to proper health and many of them do not have any health cards programmed by the government and to manage paperwork. even they do not know how the procedure is performed.